Pelaksanaan Focus Group Discussion untuk Penyiapan Materi Relationship and Sex Education pada Pelaksanaan Sekolah Perempuan - Cheris Maureta Mahar Violyn; Afifah Fitri Desyana; Jonanda Wahyu Mahendra; Zahrandy Bintang Bhaskara Argono; Vera Arista Aprilia; Amy Nurlitasari; Deaningma Maharani; Klarisa Afif Nusaibah; Vera Putri Meytasharoh; Clera Agretyas Nur Anisa; Ardhana Januar Mahardhani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The implementation of a group discussion forum (FGD) carried out in the context of preparing materials on relationships and sex education (RSE) is very important due to the limitations of the implementation group in evaluating the content. content of module documentation. The participation of several experts such as psychologists, doctors, midwives, speakers and community members are helpful in providing input for material adjustment. This FGD activity was carried out on August 30, 2023 with the implementation team BEM-FKIP Muhammadiyah University Ponorogo. The steps of the FGD activity in this activity are; (1) Prepare modules to be used in FGD, (2) Coordinate implementation of FGD activities, (3) Invite experts with CSR skills, (4) Conduct FGD and (5) Evaluate evaluate the implementation of FGD and improve learning materials. The conclusion of this activity is that multi-stakeholder participation and collaboration are important things that the team must do during the document preparation process to have appropriate and quality module document content.